Every girl gets confused [large type] : a novel - Thompson, Janice A. (Thompson, Janice A. Brides with style, 2015)
"Katie Fisher has a new boyfriend, but her ex is determined to win her back. Now she must choose between the love she thought she lost and the love she stumbled upon in the aftermath"--